Durability of Cardiometabolic Outcomes Among Adolescents After Sleeve Gastrectomy: First Study with 9-Year Follow-up - Wahiba Elhag (5245547) (2022)
Background Long-term durability of weight loss and comorbidity resolution beyond 7 years after laparoscopic sleeve gastrectomy (LSG) among adolescents is completely lacking. Methods Retrospective review of adolescents aged ≤ 18 years who underwent primary LSG at our institution between 2011 and 2015 (N = 146). We assessed anthropometric and cardiometabolic outcomes at 1, 3, 5, 7, and 9 years. Results Follow-up rates were 57.53%, 82.87%, 85.24%, 83.92%, and 83.33% at the five time points. The preoperative mean body mass index (BMI) (45.60 ± 6.50 kg/m2) decreased at year 1 (30.04 ± 4.96 kg/m2, P=0.001) and was maintained up to 9 years (30.20 ± 3.92 kg/m2, P = 0.001). Remission rates were triglycerides, 100% (11/11) at 5 years, and 100% (1/1) at 9 years; high density lipoprotein, 89.4% (17/19) at 5 years, and 100% (3/3) at 7 years; low density lipoprotein, 71.4% (11/14) and 100% (3/3) at 5 and 7 years; total cholesterol, 70% (7/10) at 5 years, and 100% (2/2) at 9 years; uric acid, 100% (3/3) at 5 years. Remission of liver enzymes was 84.6–100% (22/26–2/2) at 5–9 years. Prediabetes remission was 87.5% (14/16 and 7/8) at 5 and 7 years and 100% (3/3) at year 9. Type 2 diabetes complete remission was 50% (3/6, 1/2) at years 5 and 7, with all cases resolved at 9 years. The only case of hypertension completely resolved. Conclusions LSG achieved substantial weight loss and remission of cardiometabolic risk factors that were sustained on the long term. This is the first study among adolescents to assess such outcomes beyond 7 years. Other Information Published in: Obesity Surgery License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s11695-021-05364-3